Catalytic ceramic papers for diesel soot oxidation: A spray method for enhanced performance - Tuler, Fernando Esteban (2015)
A spraymethod is proposed to improve the catalytic properties of ceramic papers to be used as catalytic lters for removing diesel soot particles. Small particles of Ce and Co oxides, acting as active centers for the combustion of the soot retained by the lter, are efciently and homogeneously deposited. On the contrary, the application of the conventional dripmethod results in bigger particlesmainly agglomerated at the crossings between the bers of the ceramic paper. As a result, catalytic papers prepared by the spraymethod exhibitmuch higher performance with soot combustion temperatures decreased by ~30 °C.